Condições bucais e isolamento de Streptococcus mutans em pacientes submetidos à cirurgia bariátrica - Muniz, Rosina Maria Carvalho Caminha (2011)
Obesity is associated with oral diseases by promoting inflammatory processes and because of the fact that obese patients often eat cariogenic foods and use drugs capable of inducing salivary alterations. Bariatric surgery, surgical means of treating morbid obesity and obesity associated to co-morbidities, aims to change the volumetric capacity of the gastrointestinal tract and the course of the alimentary bolus. It causes changes in food consumption patterns and, often, gastro-esophageal disorders and may influence deleteriously oral health, which, however, is not determined. Objective: The aim of this study was to determine the profile of drug use, the occurrence of vomiting and tooth sensitivity, the standard of food eating and dental plaque index; to quantify Streptococcus mutans in stimulated saliva; to measure DMFT and to count erosive lesions in patients who had already been submitted to bariatric surgery and in patients who were going to be submitted to bariatric surgery, registering changes in pattern of occurrence of vomiting and tooth sensitivity and dietary patterns of patients who had already been submited to bariatric surgery. Materials and Methods: Through cross-sectional study, seeking retrospective data, there were evaluated 46 patients undergoing bariatric surgery (“Non-Operated” group) and 46 in the second year of postoperative follow-up of the same surgery (“Operated” group). After collection of personal data, we proceeded to collect saliva (to quantify S. mutans) and dental evaluation. Results: "Non-operated" group showed greater medication use and lower frequency of vomiting than "Operated” group, although, in this group, the occurrence of vomiting had reduced over time. "Operated" group had a higher intake of sweet foods and smaller intake of acid food than "Non-operated” group; the consumption of sweet foods and red meat of “Operated” group at the time of assessment decreased compared the preoperative period. Both groups had similar dental sensitivities and the majority of "Operated" group patients reported similarity of tooth sensitivity after surgery compared to preoperative values. Both groups showed similar and high plaque index (52.03 ± 14.30 for "Non-operated" group and 51.59 ± 10.38 for "Operated” group), the same was observed for S. mutans count (log (number of CFUs per mL of saliva +1) equal to 5.12 ± 0.64 for "Non-operated" group and 5.05 ± 1.06 for "Operated" group) and DMTF (13.67 ± 5.78 for "Non-operated" group 13.33 ± 5.78 for "Operated" group). Both groups were similar with respect to dental erosion variable. Discussion: Elevated plaque index, S. mutans count and DMFT show the condition of poor oral health of both patients with morbid obesity and submited to bariatric surgery, difficulting the eventually possible weight loss process by clinical means for obese patients and burdening the "new stomach" in patients undergoing surgery. Conclusion: Bariatric patient needs more attention to oral health, from oral hygiene orientation to the performance of operative procedures, providing oral health and contributing to the success of the surgical procedure.